ERP Software-As-A-Service : business model changes in South Africa - Ramotala, Tokelo (My University, 2015)
ABSTRACT The software market is changing, software vendors are moving towards offering ERP as a Software-As-A-Service (SAAS) product. South African software vendors need to be cognizant of the full implications of offering ERP SAAS and identify how it will impact their business. A smooth transition is essential for South African software vendors to be better positioned to capitalize on the growing demand for ERP SAAS. The purpose of this research was to determine how South African software vendors have changed their business model to offer ERP SAAS. The aim was to identify the major changes that software vendors experienced when transitioning from offering ERP as an on-premise system to a Software-As-A-Service model. Data was collected through conducting interviews with management, senior sales and information technology personnel who are involved in developing business models within the information technology companies offering ERP SAAS. The results of the study show that software vendors experienced changes in all the elements of their business model. Software vendors had to change their offering such that it offers a low total cost of ownership, shorter implementation time and is flexible to customer changes. They had to utilize more direct channels to deliver, market and support the ERP SAAS offering. The revenue stream from the ERP SAAS offering changed to monthly subscription fees. Key resources required include hardware and software infrastructure, as well as human resources to manage the new resources. Software vendors had to focus on simplifying the ERP SAAS offering and ensuring that it is operational 24 hours a day. The cost-structuring had to include infrastructure and labour costs. The transition from offering ERP as an on-premise system to a SAAS product has implications throughout the organization with regards to the business processes and personnel. Software vendors need to conduct thorough business planning and have large financial resources before embarking on offering ERP SAAS.
MBA 2014
Keywords: Management information systems, Integrated software, Business planning, Business enterprises